Characterizing Mesoscale Eddies of Eastern Upwelling Origins in the Atlantic Ocean and Their Role in Offshore Transport - Ioannou, Artemis; Speich, Sabrina; Laxenaire, Remi (Frontiers in Marine Science, 2022)
Motivated by the recurrent formation of eddies in the eastern upwelling areas, we examine cross-basin connectivity that is promoted by coherent, long-lived and long-propagating mesoscale eddies in the Atlantic Ocean. By applying the TOEddies detection and tracking algorithm to daily satellite observations (AVISO/DUACS) of Absolute Dynamic Topography (ADT), we characterize mesoscale eddy activity and variability in the North and South Atlantic. This method provides a robust eddy-network reconstruction, enabling the tracking of eddies formed in the Atlantic eastern upwelling systems together with any merging and splitting events they undergo during their lifetime as long as they remain detectable in the altimetry field. We show that during the years of observations, mesoscale eddies are long-lived coherent structures that can ensure oceanic connectivity between the eastern and the western boundaries, as a result of complex inter-eddy interactions. Moreover, alignment of South Atlantic eddies of eastern boundary origins with available Argo floats achieves a mean cross-basin connectivity signal from both anticyclonic and cyc5lonic eddies which is particularly evident at depth, along thermocline isopycnal layers of γn = 26 - 27 kg m–3. We explore two individual cyclonic eddy trajectories from in-situ measurements gathered by different Argo profiling floats trapped inside the eddy cores. Our results support the hypothesis that mesoscale eddies sustain and transport water masses while subducting during their westward propagation.